The mechanobiology of obesity and related diseases - Gefen, Amit; Benayahu, Dafna (Studies in Mechanobiology, Tissue Engineering and Biomaterials,, 2015)
This volume describes the state-of-knowledge in the study of the relationships between mechanical loading states in tissues and common pathophysiologies related to increase in mass of adipose tissues and/or hyperglycemia which eventually lead to obesity, diabetes, insulin resistance, hyperlipidemia, metabolic inflammations, certain types of cancer and other related diseases. There appears to be an interaction between the loading states in tissues and cells and these chronic conditions, as well as with factors such as age, gender and genetics of the individual. Bioengineering has made key contributions to this research field in providing technologies for cell biomechanics experimentation, microscopy and image processing, tissue engineering and multi-scale, multi-physics computational modeling. Topics at the frontier of this field of study include: the continuous monitoring of cell growth, proliferation and differentiation in response to mechanical factors such as stiffness of the extracellular matrix (ECM) and mechanical loads transferred through the ECM; mechanically-activated signaling pathways and molecular mechanisms; effects of different loading regimes and mechanical environments on differentiation fates of mesenchymal stem cells (MSCs) into myogenic and osteogenic versus adipogenic lineages; the interactions between nutrition and mechanotransduction; cell morphology, focal adhesion patterns and cytoskeletal remodeling changes in adipogenesis; activation of receptors related to diabetes by mechanical forces; brown and white adipose plasticity and its regulation by mechanical factors.